United Under One Roof: Artist Painters and Coarse Painters and their Relations in Seventeenth-Century Leiden - Piet Bakker (Early Modern Low Countries, 2017)
The job titles kunstschilder (artist painter) and klad- or grofschilder (coarse painter)only came into regular use after 1640. In the first decades of the seventeenth century,anyone who painted for a living was simply referred to as a schilder (painter). Thisarticle traces the way the division of the painter’s craft into two more or less separatetrades emerged, specifically for Leiden. The background against which this process isconsidered is the genesis of Leiden’s Guild of St Luke. In the art historical literature, theGuild of St Luke usually appears in its role as successful protector of the artist paintersagainst the import of paintings from other towns and cities. In most studies, theimportance of the guild is measured in terms of the composition of the local holdingsof paintings – the demand side of the art market. The difficult genesis of the LeidenGuild of St Luke provides a good opportunity to consider the importance of this guildfrom the supply side – the artists themselves.